Desenvolvimento de massas de pães congeladas tipo forma integrais adicionados de faseolamina (Phaseolus vulgaris) e açaí (Euterpe oleracea mart.) - Mendes, Selvina Deborah Souza (2022)
The search for healthier foods with functional claims is gaining more and more strength in the Brazilian market due to its importance in the fight against some diseases, such as: diabetes and hypertriglyceridemia, making the production of foods with functional claims to be increasingly growing. In this sense, the present work aimed to evaluate the technological and nutritional potential of phaseolamine and açaí powder as functional ingredients in different formulations of bread doughs, analyzing the effect in frozen bread doughs of the integral form type, on the glycemic index of the product and in pancreas ad liver tissues through in-vivo biological testing. For the development of formulations and analysis of the effect of the addition of functional ingredients, the central composite rotational design was applied. Two formulations were selected for freezing the masses, and the physical parameters, pH, acidity and proximate composition were evaluated, in different periods of time. An in vivo test was carried out to evaluate the effect of the ingredients on the glycemic index, the influence on weight, feed efficiency coefficient, glycemia and on pancreas and liver tissues of Swiss mice (Mus musculus). The formulations T6 were chosen, containing 8% of phaseolamine and 6% of açaí powder, and T11 with 8% of phaseolamine and 11% of açaí. Phaseolamine and açaí powder promoted the reduction of specific volume, expansion index, dough expansion factor and increase in bread density. Breads subjected to 60 days of freezing had their expansion factor of the standard formulation decreased but increased in formulations T6 and T11. The glycemic index did not decrease in the T6 formulations. The glycemic index does not decrease in the T6 and T11 formulations, suggesting that the differentiated percentage of açaí powder has increased the glycemic index of the pasta. In the histological analysis of the liver, no condition of hepatic steatosis was observed for the three samples, although, morphologically, they presented a slight toxicity. In the pancreas, no morphological changes of toxicity were found in the groups analyzed. It is concluded that the addition of phaseolamine and açaí powder in the formulations was satisfactory in the evaluation of the physical properties of the breads, but in relation to the glycemic index it was not possible to produce a bread with low content, since the bread in its traditional way already has a high glycemic index.